2019
DOI: 10.1016/j.ijid.2019.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Role of outer membrane permeability, efflux mechanism, and carbapenemases in carbapenem-nonsusceptible Pseudomonas aeruginosa from Dubai hospitals: Results of the first cross-sectional survey

Abstract: Objectives: Carbapenem resistance in Pseudomonas aeruginosa is growing and results from variable mechanisms. The objectives of the current study were to investigate mechanisms of carbapenem resistance and genetic relatedness of P. aeruginosa isolates recovered in Dubai hospitals. Methods: From June 2015 through June 2016, carbapenem-nonsusceptible P. aeruginosa were collected from 4 hospitals in Dubai, and subjected to antimicrobial susceptibility testing, molecular investigation of carbapenemases by PCR-seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 48 publications
(61 reference statements)
4
34
1
Order By: Relevance
“…5,[21][22][23] Class 1 integrons were detected in 14 (12.4%, 14/113) isolates, a similar finding to other research from China. 5,[21][22][23] However, this result is quite different from those of studies in which the determinants of drug resistance related to integrons were found in the isolates from several P. aeruginosa outbreaks. 6,24,25 Studies have shown that almost half of all drug-resistant P. aeruginosa strains carry integrons.…”
Section: Discussionsupporting
confidence: 89%
“…5,[21][22][23] Class 1 integrons were detected in 14 (12.4%, 14/113) isolates, a similar finding to other research from China. 5,[21][22][23] However, this result is quite different from those of studies in which the determinants of drug resistance related to integrons were found in the isolates from several P. aeruginosa outbreaks. 6,24,25 Studies have shown that almost half of all drug-resistant P. aeruginosa strains carry integrons.…”
Section: Discussionsupporting
confidence: 89%
“…After original detection in North America, VIM-7 was recently described in another report from Brazil [90]. Our group has lately detected several VIM enzymes including VIM-2, VIM-30, VIM-31, and VIM-42 from nosocomial P. aeruginosa in Dubai, United Arab Emirates [67], with VIM-2 co-existing with the Ambler class A carbapenemase GES-5. Moreover, in Lebanon, we detected VIM-2 in 16% of a nationwide collection of nosocomial P. aeruginosa that were primarily spread among different hospitals by clonal dissemination [83].…”
Section: Ambler Class B Carbapenemases (Metallo-β-lactamases)mentioning
confidence: 72%
“…Later, over 20 GES variants were described, but only a few display carbapenemase activity. For instance, P. aeruginosa from Spain [66] and Dubai [67] revealed GES-5, while P. aeruginosa from Mexico revealed GES-20 [68]. In addition, Moubareck and Colleagues identified GES-11 in an isolate of A. baumannii in France [69], and the same enzyme was identified in nosocomial isolates of this organism from Lebanon [70].…”
Section: Ambler Class a Carbapenemasesmentioning
confidence: 96%
See 1 more Smart Citation
“…In a survey from Taiwan, the rate of resistance was close to 9% [ 189 ], which was about 6% in a German university hospital [ 190 ], 5% in Spain [ 191 ], 4% in Korea [ 192 ], and 2% in Thailand [ 193 ]. In a cross-sectional, multicenter survey from Dubai, all the studied P. aeruginosa isolates were colistin sensitive [ 194 ]. On the other hand, the rate of resistance was 22% in a report from India [ 195 ], and 15% in a nationwide Italian survey [ 196 ].…”
Section: Special Features and Spread Of Polymyxin Resistance Amongmentioning
confidence: 99%